(untitled) - Masterton, William L. (Belmont, CA., 2004)
This textbook outlines the principles that govern chemical reactions and continuously illustrates their usefulness in practical applications. The authors (University of Connecticut) cover reactions in aqueous solutions, the ideal gas law, electron arrangements, rate of reaction, acid-base solutions, and complex ions. The sixth edition replaces 30% of the in-text examples, adds four research essays, and updates molecular models.
Keywords: Chemistry